Karate-do: mi camino. Autobiografía - García Díez, Juan María (Revista de Artes Marciales Asiáticas, 2012)
<span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: IT; mso-bidi-font-weight: bold;" lang="IT">Gichin Funakoshi. Madrid: Dojo Ediciones, 2007. 160 páginas. 11x18 cm. I.S.B.N.: 978-84-935400-0-5.